2005
DOI: 10.4049/jimmunol.174.9.5781
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB Mediates the Stimulation of Cytokine and Chemokine Expression by Human Articular Chondrocytes in Response to Fibronectin Fragments

Abstract: Fibronectin fragments (FN-f) that bind to the α5β1 integrin stimulate chondrocyte-mediated cartilage destruction and could play an important role in the progression of arthritis. The objective of this study was to identify potential cytokine mediators of cartilage inflammation and destruction induced by FN-f and to investigate the mechanism of their stimulation. Human articular chondrocytes, isolated from normal ankle cartilage obtained from tissue donors, were treated with a 110-kDa FN-f in serum-free culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
166
0
3

Year Published

2007
2007
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 196 publications
(180 citation statements)
references
References 38 publications
9
166
0
3
Order By: Relevance
“…Deletion from Ϫ1600 (Ϫ1600MMP-13) to Ϫ736 (Ϫ736MMP-13) upstream of the ATG of the MMP-13 promoter region shows no significant change in the basal promoter activity (Fig. 1A), consistent with our previous report with an immortalized chondrocyte cell line (30,32). Further deletion from Ϫ736 to Ϫ370 of the MMP-13 promoter (Ϫ370MMP-13) significantly reduces basal promoter activity (up to ϳ40% reduction).…”
Section: Identification Of An Elk-1 Response Element In the Distal Prsupporting
confidence: 80%
See 2 more Smart Citations
“…Deletion from Ϫ1600 (Ϫ1600MMP-13) to Ϫ736 (Ϫ736MMP-13) upstream of the ATG of the MMP-13 promoter region shows no significant change in the basal promoter activity (Fig. 1A), consistent with our previous report with an immortalized chondrocyte cell line (30,32). Further deletion from Ϫ736 to Ϫ370 of the MMP-13 promoter (Ϫ370MMP-13) significantly reduces basal promoter activity (up to ϳ40% reduction).…”
Section: Identification Of An Elk-1 Response Element In the Distal Prsupporting
confidence: 80%
“…Human adult articular chondrocytes were transiently co-transfected with a construct (pCMV-IB␣M), expressing a dominant negative form of IB␣, and the MMP-13 promoter/luciferase reporter plasmid. Expression of IB␣M blocks endogenous NFB signaling by competitively binding to NFB and preventing the release of activated NFB (18,30,32). Our results showed that exogenous expression of IB␣M dramatically inhibited the bFGF-mediated stimulation of MMP-13 promoter activity (Fig.…”
Section: Bfgf-mediated Phosphorylation Of Elk-1 At Serine 383 Is Linksupporting
confidence: 56%
See 1 more Smart Citation
“…In many cell types such as chondrocytes (55), synovial cells (56), and monocytes (30,54), signals transduced via ␣5␤1 result in cell survival, proliferation, and cytokine and chemokine expression. We show herein that the engagement of ␣5␤1 by sCD40L on U937 cells is also functionally relevant, because it induces the activation of ERK signaling pathways and the association of ␣5␤1 with the Triton X-100-insoluble fraction.…”
Section: Discussionmentioning
confidence: 99%
“…As discussed in the context of OBs, mechanical stimulation can activate NF-κB in chondrocytes [68]. Matrix protein fragments, including those from the major cartilage component collagen II, also depend on NF-κB to stimulate expression of MMPs, NO and inflammatory cytokines [69,70]. Since biologic agents that block either TNFα or IL-1β do not block OA progression [71,72], it is likely that other stimuli for NF-κB activation, in combination with non-cytokine transcriptional targets of NF-κB, cause significant cartilage destruction.…”
Section: Osteoarthritismentioning
confidence: 99%